2014
DOI: 10.1016/j.bjhh.2014.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Klotho: its various functions and association with sickle cell disease subphenotypes

Abstract: The Klotho protein, whose gene has predominant renal expression, acts in the control of serum phosphorus and 1,25-dihydroxyvitamin D3 and regulates the function of ion channels. It also participates in the mechanism of protection against oxidative stress and acts on the vascular endothelium by inducing the production of nitric oxide. Mutations that reflect defects in the Klotho gene expression may be implicated in the onset of osteonecrosis, priapism, and leg ulcers in patients with sickle cell disease, as a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Our previous study showed that there may be a familial component in its incidence, which makes the role of modifier gene polymorphisms important. Variants of the bone morphogenic protein, transforming growth factor, and annexin genes have been implicated and there is a need to examine their roles among our patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study showed that there may be a familial component in its incidence, which makes the role of modifier gene polymorphisms important. Variants of the bone morphogenic protein, transforming growth factor, and annexin genes have been implicated and there is a need to examine their roles among our patients …”
Section: Discussionmentioning
confidence: 99%
“…Variants of the bone morphogenic protein, transforming growth factor, and annexin genes have been implicated and there is a need to examine their roles among our patients. [29][30][31][32] One limitation of the present study is that it was not a prospective randomized trial. The comparison of the prevalence of AVNFH in previously untreated patients with that among patients on HU provided us an opportunity to study the role of the drug in the development of AVNFH.…”
mentioning
confidence: 99%
“…Defect in the Klotho gene protein has been implicated in the onset of osteonecrosis, priapism, leg ulcer, reduction in vitamin D synthesis, and depletion of nitric oxide in patients with SCD as a result of oxidative stress and endothelial impairment. 24 Similarly, lower plasma levels of protein C, free protein S, and nitic oxide but higher plasma levels of endothelin 1 and adrenomedullin have been associated with increased thrombotic risks 25,26…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not confirm any relationship between KL SNPs and clinical manifestations, the importance of these SNPs in SCD needs to be better elucidated. Given the relevance of this gene, as highlighted by de Souza Pacheco and Goncalves, 1 we believe that more research is needed to clarify this association.…”
mentioning
confidence: 95%
“…We read with great interest the recent review presented by de Souza Pacheco and Goncalves, 1 and we would like to briefly report our experience with Klotho ( KL ) single nucleotide polymorphisms (SNPs) and sickle cell disease (SCD).…”
mentioning
confidence: 99%